Performance measurement in intermodal freight transport systems: literature review and research agenda. (24th May 2022) - Saeedi, Hamid; Wiegmans, Bart; Behdani, Behzad
Performance measurement plays a key role in developing appropriate strategies and evaluating the achievement of objectives in an Intermodal Freight Transport System. This paper provides a critical and systematic review of the existing literature on this topic. The review is structured around dominant methodologies for performance measurement applied to different freight transport sub-domains, i.e., railway, inland waterway, port and maritime as well as their advantages/disadvantages. We further discuss the limitations of existing methods and applications, leading to several important knowledge and implementation gaps that require further research in the field.